The Effect of Academic Fraud Dimensions of Fraud Pentagon's On Accounting Students - Raffie Rafnhar; Muslimin Muslimin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to examine the factors that influence academic fraud behavior by college students accounting class 2018 National Development University "Veteran" East Java and accounting students class 2018 Airlangga University using factors namely pressure, rationalization, opportunity, competence, and arrogance called the concept Fraud Pentagon Theory. This study uses quantitative research methods. Collecting data in this study using questionnaires and data purposive sampling collection techniques. The regression model in this study is a multiple linear regression model using SPSS. The number of samples in this study was 82 students consisting of accounting students from the 2018 National Development University "Veteran" East Java as many as 40 students and accounting students from 2018 Airlangga University as many as 42 students who had taken the Accounting and Business Ethics Examination courses. The results of the study simultaneously showed that the Fraud Pentagon affected student academic fraud. Partially shows rationalization and competence to have a significantly positive influence on fraud academic. Pressure, opportunity, and arrogance have no significant effect on fraud academic.